STRUCTURES AND ACTIVITIES STUDY OF CARBOXYLESTERASE FROM THERMOPHILIC BACTERIA LOCAL ISOLATE AL17 - Novita Brigiyanti, Leyla
Carboxylesterase (carboxyl ester hydrolase, E.C 3.1.1.1) is an enzyme hydrolyzing short chain fatty ester bonds. Carboxylesterase from local isolate AL17 namely CEITB was cloned, expressed, and characterized. The gene contains of 1621 bp and encodes 340 amino acids with a molecular mass ~59 kDa. Homological analysis showed that CeITB exhibits no high homology to other carboxylesterase, with the highest homology to the Geobacillus stearothermophilus (44%). CeITB was expressed on Escherichia coli BL21 (DE3) and purified by ion metal affinity chromatography (IMAC) Ni-NTA. Crude extract of the enzyme still shows hydrolytic activity (1,1766 U/mg). The activity of purified enzyme enhanced more than 6 times (7,3190 U/mg). The enzyme showed high activity on short carbon chain substrate with the best on p-nitrophenyl acetate (C2) followed by p-nitrophenyl butyrate (C4) as substrates. On p-nitrophenyl caprylate (C8) the enzyme lost the activity more than 50% compared to that C2 and C4 substrates. The best activity of CeITB to C2 substrated was confirmed by docking analysis and measurement of cavity pocket of other carboxylesterases enzyme. The activity of CeITB is optimum at pH 8.0 and 51 oC. The activity of the enzyme was stable at 55 oC up to 24 hours incubation. The activity of the enzyme remained >80oC after 24 hour at 55 oC. However at 60 oC the activity of the enzyme was lost after 24 hours incubation. The activity of CeITB was influenced by the presence of metal ion. In the presence of 3mM Ca2+, Ni2+, Mn2+, Fe3+ ions the activity of the enzyme increased significantly. In contrast the activity of the enzyme was decreased by the presence of 3 mM Cu2+. The above results were confirmed by analysis of His loop conformation. In the presence of Ca2+and Ni2+ the distance between histidine and glutamate residues on the catalytic pocket was closer compared to that without the ion metals. Polarity of the solvent also influenced on the activity of CeITB, more polar of the solvent increased the activity of CeITB. In addition, the activity of CeITB was inhibited by the presence of EDTA, PMSF, and ?-mercaptoetanol. These suggesting that CeITB belong to metalloenzyme, serine carboxylesterase, and containing salt bridges. All of the unique properties of CeITB may propose that CeITB as an alternative enzyme for industrial application.